2014
DOI: 10.1097/ico.0000000000000089
|View full text |Cite
|
Sign up to set email alerts
|

Effect of a Mediterranean Dietary Pattern and Vitamin D Levels on Dry Eye Syndrome

Abstract: Purpose To evaluate the association between a Mediterranean dietary pattern (MeDi) and Vitamin D levels on dry eye syndrome (DES) Methods Design Cross-sectional study. Participants Male patients seen in the Miami Veterans Affairs eye clinic with normal eyelid, corneal, and conjunctival anatomy were recruited to participate in the study. Testing Patients filled out the 2005 Block Food Frequency Questionnaire (FFQ) and the Dry Eye Questionnaire 5 (DEQ5) and underwent measurement of tear film parameters.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
64
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(66 citation statements)
references
References 26 publications
2
64
0
Order By: Relevance
“…A small but favorable effect of higher vitamin D levels on DES symptoms was mentioned in another study. 23 Owing to the antiinflammatory and immunoregulatory properties of vitamin D, its deficiency may cause dryness of the eyes, which is an autoimmune and inflammatory condition. The relation between vitamin D deficiency and Ss was shown in previous studies.…”
Section: Discussionmentioning
confidence: 99%
“…A small but favorable effect of higher vitamin D levels on DES symptoms was mentioned in another study. 23 Owing to the antiinflammatory and immunoregulatory properties of vitamin D, its deficiency may cause dryness of the eyes, which is an autoimmune and inflammatory condition. The relation between vitamin D deficiency and Ss was shown in previous studies.…”
Section: Discussionmentioning
confidence: 99%
“…22 Galor et al mentioned the small but favorable effect of higher vitamin D levels on dry eye symptoms. 23 The relation between vitamin D deficiency and Ss was shown in previous studies. [1][2][3][4] AgmonLevin et al emphasized that low levels of vitamin-D correlated with the presence of peripheral neuropathy and lymphoma among PSs patients in their study.…”
Section: Resultsmentioning
confidence: 99%
“…Although it has been suggested that the severity of dry eye was not associated with vitamin D levels (Galor et al, 2014), it has been reported that dry eye symptoms (assessed with DEQ5) were reduced when vitamin D levels were higher (Galor et al, 2014). Kurtul and the colleague (2015a) assessed the association between human's serum vitamin D and dry eye measurements using TBUT and Schirmer test, they found the dry eye measurements were reduced in people with vitamin D deficiency.…”
Section: Vitamin D Is a Lipophilic Prohormone And Possesses Immunomodmentioning
confidence: 99%
“…Insufficient or deficient vitamin D level has been linked to myopia (Choi et al, 2014;Mutti & Marks, 2011), dry eye disease (Galor et al, 2014) and age related macular degeneration (Millen et al, 2011). A study of the impact of vitamin D supplements on the eye's intraocular pressure (IOP) reported no differences before and after treatment (Krefting et al, 2013).…”
Section: Vitamin D and Ocular Healthmentioning
confidence: 99%
See 1 more Smart Citation